2020
DOI: 10.1002/lsm.23310
|View full text |Cite
|
Sign up to set email alerts
|

Experience Treating Earlobe Keloids with Laser Diode 980nm Excision Followed by Triamcinolone Infiltration

Abstract: Background and Objective Lasers have a favorable synergistic effect when combined with other modalities of treatment against keloids. Different types of lasers have been used with triamcinolone infiltration, resulting in promising success rates. The purpose of this study is to describe our first experience treating earlobe keloids with 980 nm laser diode excision followed by triamcinolone infiltration and present our outcomes after 24 months of follow‐up. Study Design/Materials and Methods A retrospective char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, when used in monotherapy, laser therapy shows recurrence rates similar to conventional surgery alone (45%-100%). 5 We present a new technique for recalcitrant auricular keloids, which combines surgery, contact cryotherapy, intralesional injections of 5-FU, and TA.…”
mentioning
confidence: 99%
“…However, when used in monotherapy, laser therapy shows recurrence rates similar to conventional surgery alone (45%-100%). 5 We present a new technique for recalcitrant auricular keloids, which combines surgery, contact cryotherapy, intralesional injections of 5-FU, and TA.…”
mentioning
confidence: 99%
“…14 with recurrence rates paralleling those of traditional surgical excision alone, ranging from 45% to 100%. 15 The combination of various laser types with other treatment methods, including triamcinolone acetonide (TA), has led to encouraging success rates. Recent research has suggested that the combination of intralesional steroids with laser treatment enhanced efficacy and reduced recurrence rate.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has suggested that the combination of intralesional steroids with laser treatment enhanced efficacy and reduced recurrence rate. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations